Green Marketing Dan Keputusan Pembelian Produk Organik : Pendekatan Theory Of Planned Behavior - Dewi, Isti Riana; Hidayah, Asmi Ayuning (Universitas Sultan Ageng Tirtayasa, 2024)
Green economy can be done in several ways such as product reuse, recycling, good selection of raw materials, product design, production, and consumption. In terms of consumption, Indonesian people currently tend to prefer buying organic products. During the last pandemic, only 39.51% of consumers did not consume organic products. Although the price is more expensive but does not reduce the current consumption power. According to the Indonesian Organic Agriculture Statistics, the distribution of consumers in buying organic products in West Java is quite high when compared to other regions. This think about clarifies that green promoting features a positive impact on obtaining choices for natural items and demeanors towards the environment. At that point, the demeanor towards the environment incorporates a positive impact on the choice to buy natural items. Also, attitudes towards the environment mediate green marketing and purchasing decisions for organic products.